Real-time management of river systems by using a hydrodynamic model with optimisation - Visser, Alwyn Jacobus Christiaan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.